Classical approaches to the study of religion aims, methods, and theories of research : introduction and anthology - Waardenburg, Jean Jacques 1930-2015 (De Gruyter, 2017)
Jacques Waardenburg’s Classical Approaches to the Study of Religion, first published in 1973 and updated in 1999, was groundbreaking in establishing religious studies as an independent academic field. The volume consists of two parts. The first is Waardenburg’s magisterial essay tracing the rise and development of the academic study of religion from the mid-nineteenth to the mid-twentieth century, outlining the establishment of the discipline, its connections with other fields, religion as a subject of research, and perspectives on a phenomenological study of religion. The second part comprises an anthology of texts from 41 scholars whose work was programmatic in the evolution of the academic study of religion. The pieces selected for this volume were taken from the discipline of religious studies as well as from related fields, such as anthropology, sociology, and psychology, to name a few. Each chapter presents a particular approach, theory, and method relevant to the study of religion. This second edition also includes a new foreword by Russell McCutcheon. This pioneering work is essential reading for any student of religion
Keywords: Geschichte 1850-1950; Religious education; Religionswissenschaft; Forschung; Aufsatzsammlung